Mechanism of Action, Resistance, Synergism, and Clinical Implications of Delamanid Against Multidrug-Resistant Mycobacterium tuberculosis - Khoshnood, Saeed; Taki, Elahe; Sadeghifard, Nourkhoda; Kaviar, Vahab Hassan; Haddadi, Mohammad Hossein; Farshadzadeh, Zahra; Kouhsari, Ebrahim; Goudarzi, Mehdi; Heidary, Mohsen (Frontiers in Microbiology, 2021)
Multidrug-resistant (MDR) isolates of Mycobacterium tuberculosis (MTB) remain a primary global threat to the end of tuberculosis (TB) era. Delamanid (DLM) is a nitro-dihydro-imidazooxazole derivative utilized to treat MDR-TB. DLM has distinct mechanism of action, inhibiting methoxy- and keto-mycolic acid (MA) synthesis through the F420 coenzyme mycobacteria system and generating nitrous oxide. While DLM resistance among MTB strains is uncommon, there are increasing reports in Asia and Europe, and such resistance will prolong the treatment courses of patients infected with MDR-TB. In this review, we address the antimycobacterial properties of DLM, report the global prevalence of DLM resistance, discuss the synergism of DLM with other anti-TB drugs, and evaluate the documented clinical trials to provide new insights into the clinical use of this antibiotic.